2013
DOI: 10.1093/rheumatology/ket179
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new regulatory CD4+ T cell subset in primary Sjogren's syndrome

Abstract: The present data demonstrate that circulating CD4(+) cells expressing GITR, but with low levels of CD25 (CD4(+)CD25(low)GITR(+)), are detectable in pSS patients. These cells, displaying Treg phenotype and function, are present in SG inflamed tissues and are expanded in the PB of subjects with inactive disease. Data suggest that the expansion of CD4(+)CD25(low)GITR(+) cells in pSS may represent a counter-regulatory attempt against autoimmune-driven inflammation and may provide a new target for future treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 52 publications
4
50
0
2
Order By: Relevance
“…Taking into account the pivotal role of GCs in driving B-and Tcell activation, it has been suggested that their presence in the pSS glandular infiltrates may affect the clinical picture and the progression of the disease in several ways [57]: (i) the higher degree of lymphocytic organization may lead to a more pronounced disruption of glandular architecture and secretory function impairment [31,58]; (ii) GC formation may increase lymphocyte activation and function, autoantibody production [57], and immune complex formation, leading to extraglandular manifestations [57][58][59]; and (iii) the development of B-cell NHL seems to rely on antigen-driven stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the pivotal role of GCs in driving B-and Tcell activation, it has been suggested that their presence in the pSS glandular infiltrates may affect the clinical picture and the progression of the disease in several ways [57]: (i) the higher degree of lymphocytic organization may lead to a more pronounced disruption of glandular architecture and secretory function impairment [31,58]; (ii) GC formation may increase lymphocyte activation and function, autoantibody production [57], and immune complex formation, leading to extraglandular manifestations [57][58][59]; and (iii) the development of B-cell NHL seems to rely on antigen-driven stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence, and sometimes predominance, of T cells in salivary gland infiltrates underscores their potential contribution to the pathogenesis of pSS [29,[31][32][33], growing evidence suggest a central role of B cells in the development of the disease [34]. Indeed, B lymphocyte hyperactivity and prolonged B-cell survival as well as their aberrant activity may lead to the development of NHL [2,35].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has studied CD4 + CD25 low− GITR + cells in patients with Sjögren syndrome and SLE [18,88]. Surprisingly, the number of CD4 + CD25 low/− GITR + cells in some of these patients was much higher than that of healthy controls.…”
Section: In Vivo Expansion Of Gitr + Tregs: a Potential Approachmentioning
confidence: 96%
“…1722 An expansion of CD4 + CD25 (low) GITR (+) T reg cells has been detected in inflamed tissues of the salivary glands of Sjögren syndrome patients. 53,54 This expansion may represent a regulatory attempt to reduce excessive inflammation. 5355 We hypothesize that severe inflammatory DED seen in the elderly is associated with a lack of sufficient number and/or function of ocular surface-resident T reg cells, an increase in the number and/or function of ocular surface-resident proinflammatory CD4 + Th1/Th17 cells, and a high basal level of proinflammatory mediators, such as metaloproteinases (MMPs) produced by ocular surface dendritic cells (DCs).…”
Section: Potential Immunopathological Mechanisms That Lead To Severe mentioning
confidence: 99%